Survey Research on Lecturer Performance Profiles During Pandemic Covid-19 - Dumiyati Dumiyati; Muhammad Yusuf (Procedia of Social Sciences and Humanities, 2021)
This study aims to describe the performance profile of lecturers based on the results of monitoring and evaluation of the implementation of teaching, research and community service activities during the Covid-19 pandemic. Data collection techniques used survey methods on the implementation of teaching learning process and documentation techniques in the form of lecturer performance targets and reports. Research respondents were all 216 students of the Economic Education Study Program at Unirow Tuban. Data analysis techniques used descriptive data analysis by calculating the percentage of respondents' answers, average score and categorization. The findings of the study showed that the average score was 3.7 be at interval <3.5 X <4.5, the teaching performance of the lecturers was in good category. International journal publications are very low and lecturer performance on community service in enough cathegory. The results of this study can be used to follow up on learning improvements and make online learning more effective and improve the performance of lecturers in the field of research and community service activities during the Covid-19 pandemic.